Goods and services tax (GST) and its potential impacts on Malaysian inflation - Nurliyana, Zainol (2018)
A modem consumption tax known as Goods and Services Tax (GST) or Value Added Tax (VAT) is an indirect tax levied at every stage of production chain. Malaysian GST was introduced on 11' April 2015 with the introductory rate of 6 percent consisting of the standard rate, zero-rate and exempted rate type. Various research has been done to study the economic impact of GST. This study examines the potential impacts of GST in Malaysia with the focus on the inflationary effect towards the economy. The statistical analysis utilized a combination of monthly data spanning from year 2015 to 2018, and forecast data, to measure the objectives of the research in investigating whether Malaysian GST will be inflationary or otherwise. The analysis was conducted to empirically determine the inflationary impact of GST in the short term and long term using Autoregressive Distributive Lagged (ARDL) approach through Bound Testing together with other explanatory variables in the framework of a combination of structuralist, monetarist and fiscalist elements in the model namely unemployment rate, money supply, and import. The Augmented Dickey Fuller (ADF) unit root test was applied to identify the stationary properties of the tested time series variables. The empirical results found cointegration in the series, and the study reveals that the inflation will increase by approximately 0.49 percent in the short run and 0.11 percent in the long run as a result of GST. Lastly, the CUSUM and CUSUMQ graphs confirm that the estimation is structurally stable. The findings shed new insight and lay out a clear picture for Malaysian regarding the inflationary impacts of GST.